(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In the post-independence period, the industrial sector has been crucial to the growth of India’s economy. The 1948 industrial policy resolution marked a significant breakthrough, and although subsequent reforms were introduced, the most transformative changes have occurred since 1991. These changes, which included liberalizing and deregulating the industrial sector, were driven by economic necessities but made possible through political processes. Economic activities are inherently tied to political requirements, necessitating appropriate political conditions at both state and local levels. This paper investigates the various stages of industrial development in India, emphasizing the political influences that shaped each phase. By viewing these developments through a political lens, we can gain a deeper understanding of the complexities and the ongoing nature of industrial growth in India. The study highlights that industrial development is a dynamic process influenced by numerous political, economic, and social factors, rather than just a series of policy decisions.